ISOLATION AND IDENTIFICATION OF Lentinula edodes FROM THE IRAQI ‎ENVIRONMENT AND STUDY OF THE OPTIMAL CONDITIONS FOR ITS GROWTH - Farhan, Ekhlas; Chechan‎, Rukaibaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The recent research aims to collect fungal fruiting bodies from the Iraqi environment / Baghdad Governorate /Al-Salihiya and diagnose them morphologically and molecularly using the polymerase chain reaction (PCR) technique.The fruiting bodies obtained from wild mushrooms were subjected to quantitative and qualitative analysis using HPLC to detect biologically active phenolic compounds in the fungus. The effect of some physical factors and conditions on the growth rate of fungal mycelium and its density was also studied in terms of (temperature, pH, type and concentration of materials used in preparing the media in addition to the effect of light and darkness factors). The results of BLAST analyses showed that there is a 99% match between the genes of the local isolate and the fungal strains belonging to the edodes species. This local isolate is designated by the symbol (EkRu-Bagadad-1) and the sequence (OM432157). Regarding the phenolic compounds profile, the results showed that the mushroom contains 15 phenolic compounds, which included 6 phenolic acids (Vanillic, Chlorogenic, 4-hydroxyl benzoic, Caffeic, Gallic, Cinnamic,) and 9 flavonoids (catechol, cinnamaldehyde eugnol, quercetin, nigellone, rutin, Pyrogallo, lignans, kaempferol). The total phenolic compounds in the mushroom amounted to 661.64 mg/L, and 4-hydroxybenzoic acid was the most concentrated phenolic acid in the mushroom. The results also showed that the highest growth rate of radial mycelium of the local strain of Shiitake mushroom was achieved in potato peel medium at concentrations of 20 gl-1 , which reached (0.473 cm/day). The local strain under study recorded the highest growth rate in all culture media used at pH (6) and temperature 23 C. The results also showed that the growth rate in the dark was higher than the growth rate in the light in all natural media used.